Pendampingan UMKM untuk Memenangkan Pasar Keripik Debog Pisang Online Melalui Manajemen Pengemasan Inovatif dan Pemasaran Berbasis E-Commerce - Amellia, Dhea; Pujianto, Wahyu Eko (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The problem that exists in Asman Jahe MSMEs is that the marketing strategy for banana debog chips products still uses traditional and simple methods because business owners do not understand online marketing and the product packaging process is less attractive. The purpose of this community service activity is to provide training related to product packaging management and e-commerce-based marketing that is good and attractive. Activities are carried out using direct observation and interview methods. The results of this community service activity provide solutions to MSMEs in the form of increased understanding and skills in promotional activities, the availability of hygienic, economical, clean and neat packaging, the availability of brands on packaging with attractive designs and complete information and the availability of social media as media for partners in carrying out promotional activities.